Application of Guided Imagery Therapy to Improve Sleep Quality in the Elderly: A Case Study - Ni Luh Emilia; Ni Putu Angelina (PT.Mantaya Idea Batara, 2023)
Poor sleep quality is often experienced by the elderly, so it is necessary to get attention with specific strategies and techniques in solving problems. Guided imagery therapy is one of the right choices. Based on this, this study aims to determine the effect of implementing guided imagery therapy in improving sleep quality. The research design of this case study was descriptive with 1 respondent. Data collection was carried out by means of interviews, observation and physical examination. The research instrument is the PSQI assessment format. Data reduction, presentation and conclusion is the data analysis that will be carried out. The results, after 4 sessions of therapy, it was found that the quality of the client's sleep improved with the data the client said the client felt calm regardless of the client's thoughts that it was difficult to start sleeping and the PSQI results before therapy were 10 with moderate sleep quality problems and after therapy it became 7 with mild sleep quality problems. The conclusion from this case study is that sleep quality improves. It is expected that nursing care with the implementation of guided imagery therapy can be applied in nursing activities, especially the elderly community by considering the type of sleep quality, length and time of administration so that it really becomes effective in overcoming sleep pattern disturbances.